Les nouvelles constitutions africaines et la politique internationale : contribution à une économie internationale des biens politico-constitutionnels - Sindjoun, Luc (Études internationales, 1995)
Africa's new constitutions have arisen from a dynamic of relative globalization in an era of Western preeminence. Thus, they are both barometers and instruments of international policy. The method of constitutional ecology can be used to measure the impact of international policy by examining the degree to which human rights have been firmly entrenched in Africa's new constitutions. It is also possible to measure the relative extent to which the international viewpoint has been taken into account in the internal order. As "barometers", the instrumentality of Africa's new constitutions is in relation to their being templates of the international legal order. Hence the principle of constitutionality (or "constitutional bases") of official diplomacy.